EFL Learners' Perceptions on Schoology Use in the Reading Class - Ahmad Ridho Rojabi (Universitas Hamzanwadi, 2021)
Abstract Online learning that is integrated into face-to-face learning called blended learning is believed to be more useful than online learning or face-to-face learning. Schoology is one of the online learning platforms exploited in blended learning that can help teachers to manage classroom information. Schoology allows students and teachers to share information and provides access to content or administrative features of specific courses. This study aims to investigate students' perceptions of blended learning via Schoology in reading class. This is a descriptive study, the participants of this study consisted of 28- second-semester students at the English Language Study Program, Faculty of Tarbiyah, and teacher training IAIN Jember, East Java Indonesia. The Data were collected through questionnaires and interviews. The findings of this study revealed that there were positive perceptions of blended learning via Schoology in the reading comprehension class as well as the positive learners’ attitude. Furthermore, the students agreed that Schoology in blended learning in the reading comprehension class is useful, helpful, and effective. Moreover, from the results of the interviews, there were positive aspects of blended learning via Schoology in reading comprehension which gave more benefits to engage and motivate students’ learning activities, students’ performances, learners’ autonomy, as well as students’ learning outcomes. Keywords: attitude, blended learning, perception, reading comprehension, Schoology